A study on the role of footwear as a cause of foot eczema using patch test - Neema Sandra Dias; B Nanda Kishore; D Sukumar (Wolters Kluwer Medknow Publications, 2020)
Background: Foot eczema is an allergic contact dermatitis which runs a chronic course due to the ignorance of the causative agent. Patch test is a safe and simple outpatient diagnostic procedure for all kinds of allergic contact dermatitis. Aims and Objectives: This study was done to find the role of footwear as a cause of foot eczema and to know the most common allergen in the footwear causing foot eczema by Patch testing. Materials and Methods: A total of 71 patients were enrolled in the study who presented with foot eczema. Meticulous history was taken and clinical examination was done on all patients. A patch test using Indian footwear series containing 15 allergens was performed, and results were recorded after 48 h. Results: In our study comprising 71 patients, age of the patients ranged from 13 to 70 years with a slight female preponderance. Plantar surface of foot was the most common site involved (35.2%) with a winter aggravation (21.1%). A total of 63.4% of patients were tested positive for one or more allergens present in the footwear. Footwear was reported to be an inciting agent in 36.4% patients, and 82.6% of these were tested positive. Black rubber mix (22.53%), nickel (14.08%), and colophony (12.67%) were the most common sensitizers. Conclusion: A significant incidence of footwear as a causation of foot eczema was concluded, with rubber and metals being the most common allergens. It is noteworthy to consider employing patch test routinely to know the causation of footwear in the foot eczema so that appropriate footwear can be used. However, it would be helpful if we could detect the specific allergen in a footwear to help these patients suffering a relapsing chronic dermatitis.